2022
DOI: 10.1002/hsr2.489
|View full text |Cite
|
Sign up to set email alerts
|

The role of NK and NKT cells in the pathogenesis and improvement of multiple sclerosis following disease‐modifying therapies

Abstract: Background Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system (CNS) that T cells become autoreactive by recognizing CNS antigens. Both innate and adaptive immune systems are involved in the pathogenesis of MS. In recent years, the impact of innate immune cells on MS pathogenesis has received more attention. CD56bright NK cells, as an immunoregulatory subset of NK cells, can increase the production of cytokines that modulate adaptive immune responses, whereas CD56dim NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…Based on the assumption that pregnancy is protective against disease activity while postpartum increases the risk of MS reactivation [ 16 ], our data would be in line with the literature, confirming the protective effect of a higher percentage of NK cells on MS. Considering these data, we could confirm the hypothesis that NK cells play a role in the regulation of immunotolerance and thus in the pathogenesis of MS, as previously postulated [ 5 ], and that their alteration may indeed modify the course of the disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on the assumption that pregnancy is protective against disease activity while postpartum increases the risk of MS reactivation [ 16 ], our data would be in line with the literature, confirming the protective effect of a higher percentage of NK cells on MS. Considering these data, we could confirm the hypothesis that NK cells play a role in the regulation of immunotolerance and thus in the pathogenesis of MS, as previously postulated [ 5 ], and that their alteration may indeed modify the course of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, NK cells also appear to be involved in the control of the effector functions of T cells: the reduced immunoregulatory function of these cells could be one of the driving forces in the pathogenesis of autoimmune diseases, such as MS. To date, few studies have explored the effects of anti-CD20 drugs on NK cells in MS patients, and the available results are conflicting [ 4 ]. It has recently been found that some therapies used in MS, such as Natalizumab, Fingolimod, Interferon alpha, and autologous marrow transplantation, increase the number of NK cells [ 5 ]. In addition, therapies, including Glatiramer acetate, Vitamin D3, Dimethylfumarate, Monomethylfumarate, Natalizumab, Ocrelizumab, and IFN-β, have been shown to increase the biological activity of NK cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NK and NKT cells have a very important role in immune homeostasis, as they express inhibitory and/or activating receptors that allow these cells to identify potential hazardous target cells and kill them, including activated autoreactive T cells [30,31]. The most immature NK cells, CD56 bright , are described to act mostly through cytokine production, while CD56 dim mediate their cytotoxicity in a contact-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of MS increases with CD56 bright NK cells, as these cells promote intensive secretion of cytokines (INF-γ, TNF-α, and IL-10) and adaptive immune response, whereas CD56 dim is closely associated with cytolysis. These immunoregulatory functions have been reported in clinical trials in patients (Kucuksezer et al, 2021;Ahmadi et al, 2022). Some drugs, such as daclizumab, participate in the control of MS because of their association with the inhibition of the marker CD56 brigh (Ruiz et al, 2019).…”
Section: Role Of Nk Cells In Msmentioning
confidence: 86%